Unlocking agricultural trade potential in the BIMSTEC region: Policy challenges and implications - Kamar, Abul; Roy, Devesh (International Food Policy Research Institute, 2023)
The Bay of Bengal Initiative for Multi-Sectoral Technical and Economic Cooperation (BIMSTEC) is a regional organization that comprises seven nations, five of which are from South Asia (Bangladesh, Bhutan, India, Nepal, Sri Lanka) and two from Southeast Asia (Myanmar and Thailand). BIMSTEC aims to increase trade including agri-food products to much higher levels than its historical low values lying much below potential. In 2020, intra-BIMSTEC trade accounted for a mere 6.15% of the total trade among its member countries. In contrast, intra-ASEAN trade made up around 23% of the total trade within the Association of Southeast Asian Nations (ASEAN). These figures highlight the significant room for growth in intra-regional trade among BIMSTEC member countries. Importantly the low share of intra BIMSTEC trade is not due to greater integration with supra-BIMSTEC partners. This policy note seeks to spell out some of the key agricultural trade policy-related challenges in the BIMSTEC region and their implications for economic integration in the area.